ANALISIS PENGARUH VARIABEL LEADING ECONOMIC INDICATOR (LEI) DAN COINCIDENT ECONOMIC INDICATOR (CEI) TERHADAP RETURN SAHAM JAKARTA ISLAMIC INDEX (JII) (Studi Pada Saham Jakarta Islamic Index (JII) Periode Bulan Januari Tahun 2004 Sampai Bulan Desember Tahu - Rahman, Mochamad Husin; Arfianto, Erman Denny (Diponegoro Journal of Management, 2016)
The effect of systematic risk that came from macroeconomic variables can not be eliminated in Sharia Capital Market. Therefore, investor must consider the macroeconomic variables to invest in Sharia Capital Market. The purpose of this study is to analyze the effect of Leading Economic Indicator (LEI) and Coincident Economic Indicator (CEI) variables on Jakarta Islamic Index (JII) Stock Return. LEI variables includes Export, Exchange Rate, Consumer Price Index, Industrial Production Index and Arrival Number of Foreign Tourist meanwhile CEI variables includes Retail Sales and Money Supply.            The sample used in this study is a secondary data of Jakarta Islamic Index (JII) Stock closing price, Export, Exchange Rate, Consumer Price Index, Industrial Production Index, Arrival Number of Foreign Tourist, Retail Sales and Money Supply on Januari 2004-Desember 2014 period. This study uses Multiple Linier Regression Analysis as the analysis method.             The result of this study indicate that the Leading Economic Indicator (LEI) and Coincident Economic Indiacator (CEI) variables simultaneously affect the Jakarta Islamic Index Stock Return. Then the partial testing shows the Exchange Rate has a negative and significant effect on Jakarta Islamic Index Stock Return. Meanwhile Arrival Number of Foreign Tourist and Consumer Price Index variables have a positive and significant effect on Jakarta Islamic Index Stock Return.